Neoadjuvant chemotherapy-induced decrease of prognostic nutrition index predicts poor prognosis in patients with breast cancer - Takaaki Oba; Kazuma Maeno; Daiya Takekoshi; Mayu Ono; Tokiko Ito; Toshiharu Kanai; Ken-ichi Ito (BMC Cancer, 2020)
Abstract Background The prognostic nutritional index (PNI), which is an easily calculated nutritional index, is significantly associated with patient outcomes in various solid malignancies. This study aimed to evaluate the prognostic impact of PNI changes in patients with breast cancer undergoing neoadjuvant chemotherapy (NAC). Methods We reviewed patients with breast cancer who underwent NAC and a subsequent surgery for breast cancer between 2005 and 2016. PNI before and after NAC were calculated using the following formula: 10 × serum albumin (g/dl) + 0.005 × total lymphocyte count/mm3. The relationship between PNI and prognosis was retrospectively analyzed. Results In total, 191 patients were evaluated. There was no significant difference in disease-free survival (DFS) between the pre-NAC PNI high group and the pre-NAC PNI low group (cutoff: 53.1). However, PNI decreased in 181 patients (94.7%) after NAC and the mean PNI also significantly decreased after NAC from 52.6 ± 3.8 pre-NAC to 46.5 ± 4.4 post-NAC (p < 0.01). The mean ΔPNI, which was calculated as pre-NAC PNI minus post-NAC PNI, was 5.4. The high ΔPNI group showed significantly poorer DFS than the low ΔPNI group (cut off: 5.26) (p = 0.015). Moreover, high ΔPNI was an independent risk factor of DFS on multivariate analysis (p = 0.042). Conclusions High decrease of PNI during NAC predicts poor prognosis. Thus, maintaining the nutritional status during NAC may result in better treatment outcomes in patients with breast cancer.